World Bank East Asia and Pacific Economic Update, October 2019 : Weathering Growing Risks - World Bank (Washington, DC: World Bank, 2019)
Growth in the developing East Asia and Pacific region slowed in the first half of 2019 given weakening global demand and heightened policy uncertainty amid ongoing trade tensions. Steady consumption growth helped to partly offset the effects of weakening exports and investment on growth. The region’s growth prospects face intensified downside risks, including further escalation of trade disputes, a sharper-than-expected slowdown in China, the United States and the Euro Area, along with a disorderly Brexit, and an abrupt change in global financing conditions. In some countries, rising indebtedness and other vulnerabilities, such as the constrained capacity for foreign debt rollover, could amplify the negative effects of external shocks. The regional growth moderation underscores the need to address key vulnerabilities and preserve economic dynamism among developing East Asia and Pacific economies. In the short run, countries with sufficient policy space should use available policy tools to stimulate domestic activities. Better quality spending, together with prudent debt management, is needed to safeguard fiscal sustainability. Deepening regional integration would help offset the negative impact of global protectionism. In the medium to long term, pursuing structural reforms that raise competitiveness, support trade and investment, and encourage innovation is critical to boosting productivity and growth.